Pengaruh Blog Edukatif Tentang Hipertensi Terhadap Pengetahuan Tentang Hipertensi dan Perilaku Diet Hipertensi pada Pasien Hipertensi di Wilayah Kerja Puskesmas Wirobrajan Yogyakarta - Firmawati, Erfin (Universitas Muhammadiyah Yogyakarta, 2015)
Background: Hypertension is one of the noncommunicable diseases which is still a major problem around the world because of its prevalence remains high and continues to rise. Increasing prevalence of hypertension is caused by many factors including lack of knowledge about hypertension and unhealthy dietary behavior. One of the eff ort to improve the knowledge and dietary behavior is providing health education with the use of electronic media through utilization of educational blog.Porpose: the aims of this study were to determine the eff ect of the educational blog about hypertension on the knowledge of hypertensive and hypertension dietary behavior of the patients in Wirobrajan Public Health Care Center of Yogyakarta.Method: This research used Quasi Experiment with one group pre-post test design. The total samples were 21 respondents that taken by purposive sampling method. Statistical tests that used was Wilcoxon Signed Ranks Test with signifi cance level p 0.05 level to analyze knowledge about hypertension and Paired t Test to analyze dietary behaviors of hypertension.Result: The results showed that there were a signifi cant eff ect to the knowledge about hypertension (Z=-3.639, p=0,00) and dietary behavior of hypertension (t = -6,185, p =0,00) after providing educational blog about hypertensionConclution:There were eff ects of educational blog about hypertension on the knowledge about hypertension and dietary behaviors of hypertension of hypertensive patient in Wirobrajan Public Health Care Center of Yogyakarta.Keywords: educational blog, hypertension, knowledge, and dietary behavior.